WDR76 is a RAS binding protein that functions as a tumor suppressor via RAS degradation - Jeong, Woo-Jeong; Park, Jong-Chan; Kim, Woo-Shin; Ro, Eun Ji; Jeon, Soung Hoo; Lee, Sang-Kyu; Park, Young Nyun; Min, Do Sik; Choi, Kang-Yell (Nature communications, 2019)
Stability regulation of RAS that can affect its activity, in addition to the oncogenic mutations, occurs in human cancer. However, the mechanisms for stability regulation of RAS involved in their activity and its roles in tumorigenesis are poorly explored. Here, we identify WD40-repeat protein 76 (WDR76) as one of the HRAS binding proteins using proteomic analyses of hepatocellular carcinomas (HCC) tissue. WDR76 plays a role as an E3 linker protein and mediates the polyubiquitination-dependent degradation of RAS. WDR76-mediated RAS destabilization results in the inhibition of proliferation, transformation, and invasion of liver cancer cells. WDR76 −/− mice are more susceptible to diethylnitrosamine-induced liver carcinogenesis. Liver-specific WDR76 induction destabilizes Ras and markedly reduces tumorigenesis in HRas G12V mouse livers. The clinical relevance of RAS regulation by WDR76 is indicated by the inverse correlation of their expressions in HCC tissues. Our study demonstrates that WDR76 functions as a tumor suppressor via RAS degradation. Overexpression of RAS proteins is frequently observed in patients with hepatocellular carcinoma. Here, the authors identify an HRAS binding protein, the E3 ubiquitin ligase WDR76, which promotes HRAS degradation, thus functioning as a tumour suppressor in liver cancer